Engineering communication - Knisely, Charles W. (Cengage Learning, 2015)
A guidebook for creating clear, accurate and engaging communication. It is a complete teaching tool that includes the use of technology to produce dynamic written, oral, and visual communication. It features numerous complete examples, many taken directly from either student or business samples